2004
DOI: 10.1103/physrevb.70.115204
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the phosphorus-vacancy complex in silicon: A resonant-bond model

Abstract: All material supplied via Aaltodoc is protected by copyright and other intellectual property rights, and duplication or sale of all or part of any of the repository collections is not permitted, except that material may be duplicated by you for your research use or educational purposes in electronic or print form. You must obtain permission for any other use. Electronic or print copies may not be offered, whether for sale or otherwise to anyone who is not an authorised user.Powered by TCPDF (www.tcpdf.org) Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Quantum mechanical treatments of periodic cells containing the defects by several groups using the local density approximation (LDA) have universally had difficulty in coming up with these results, predicting ''resonant bond'' distortions for the EPR-active charge states [5][6][7][8]. This has led to a challenge by the theorists involved as to whether the interpretation of the EPR results were correct.…”
Section: Introductionmentioning
confidence: 94%
“…Quantum mechanical treatments of periodic cells containing the defects by several groups using the local density approximation (LDA) have universally had difficulty in coming up with these results, predicting ''resonant bond'' distortions for the EPR-active charge states [5][6][7][8]. This has led to a challenge by the theorists involved as to whether the interpretation of the EPR results were correct.…”
Section: Introductionmentioning
confidence: 94%
“…On the modelling side, the energy ranking of these configurations is not consistent between different studies [11][12][13][14][15][16] : the ground state geometry for the PV center was found to be a pairing configuration for both neutral and negative charge states in [11] (see also Ref. 12 for the neutral charge state) but a resonant one in [13].…”
Section: Introductionmentioning
confidence: 85%
“…However, Watkins speculated that their defect-induced optical bands should be very similar to AsV − . Even though the electronic structure of the E center is a clear evidence of the Jahn-Teller effect, no quantitative description has so far been given due to the limitations of previously used mean-field approaches [11][12][13][14][15][16] .…”
Section: Ground State Electronic Structure: Confirmation Of the mentioning
confidence: 99%
“…As a result, the symmetry of atomic relaxation pattern near a defect not necessarily reproduces the global lattice symmetry. Wellknown examples of this situation are met with divacancy [2,[4][5][6][7][8][9] and E-centres [1,10,11] in silicon. Moreover, sometimes the atomic potential energy surface can have more than one local minimum, corresponding to different relaxation patterns [9].…”
Section: Introductionmentioning
confidence: 99%